Sanfilippo syndrome type D in two adolescent sisters. Issue 6 (June 1991) - Siciliano, L; Fiumara, A; Pavone, L; Freeman, C; Robertson, D; Morris, C P; Hopwood, J J; Di Natale, P; Musumeci, S; Horwitz, A L
Abstract : We report on two adolescent sisters with Sanfilippo syndrome type D with some clinical features different from other cases previously described. They are the oldest cases reported to date and provide new clues about the course of the disease. Enzymatic and immunological characterisation of the patients' fibroblasts indicated deficiency of N-acetylglucosamine-6-sulphate sulphatase (GlcNAc-6S sulphatase). However, Northern blot analysis showed apparently normal mRNA encoding GlcNAc-6S sulphatase. These findings suggest that abnormal translation or premature degradation may be responsible for the enzyme defect in these cases of Sanfilippo syndrome type D.